A Hybrid Technique for Order Preference in Decision-Making. (15th February 2015) - Beg, Ismat; Rashid, Tabasam
Abstract : We propose a hybrid technique by merging fuzzy version of the classical technique for order preference by similarity to ideal solution and decision-making trial and evaluation laboratory technique for trapezoidal fuzzy numbers, where interaction phenomena among the decision-making problem and weights are taken into account. The feasibility of this new method is demonstrated by applying it to an example.